2021
DOI: 10.1016/j.cognition.2021.104893
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the way from the unknown to the known: The role of convex hull shape in numerical comparisons

Abstract: Various studies have shown that numerical processing is modulated by non-numerical physical properties. One such physical property is the convex hull -the smallest convex polygon surrounding all items in an array. The convex hull is usually discussed only in terms of its area. However, our group has shown that observers use the convex hull shape, as defined according to the number of vertices of the convex hull, to make numerical estimations (Katzin et al., 2020). Yet, it is still unknown if and how the convex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Another example comes from our own experience. We lately suggested that the shape of the convex hull is important for numerical judgments (Katzin et al, 2019;Shilat et al, 2021). Previous studies have not recorded data on the shape of the convex hull and have not provided their stimuli.…”
Section: Stimuli Control In Non-symbolic Numerical Comparison Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Another example comes from our own experience. We lately suggested that the shape of the convex hull is important for numerical judgments (Katzin et al, 2019;Shilat et al, 2021). Previous studies have not recorded data on the shape of the convex hull and have not provided their stimuli.…”
Section: Stimuli Control In Non-symbolic Numerical Comparison Studiesmentioning
confidence: 99%
“…Accordingly, intrinsic properties describe information extracted from individual array items. In contrast, extrinsic properties describe information extracted from the array as a whole (Shilat et al, 2021). In case of disagreement between annotators, extrinsic properties were considered relational, and intrinsic as non-relational (Lewis, 1983;Marshall & Weatherson, 2023).…”
Section: Controlled Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…First, it has been shown that participants are able to process several visual parameters. In particular, scholars have manipulated several visual features and identified partial (in)congruency and full (in)congruency conditions [30,36]. In partial (in)congruency conditions, arrays were (in)congruent in one of the controlled visual features (e.g., cumulative area), while in fully (in)congruency conditions, arrays were (in)congruent on all controlled visual properties [30].…”
Section: Introductionmentioning
confidence: 99%